1972
DOI: 10.1139/v72-554
|View full text |Cite
|
Sign up to set email alerts
|

The Triplet State of Ketones in Solution: Quenching of Triplet Acetone by Amines

Abstract: Rateconstants for quenching of triplet excited acetone by primary and tertiary amines in solution have been measured directly by flash and pulsed laser techniques. The rate constants were found to be independent of solvent dielectric constant over the range E 1.9 to e 80, but were influenced by amine ionization potential. The results are interpreted as supporting a charge-transfer model for the quenching of triplet ketones by tertiary amines. The intervention of free ions in the quenching process is discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Tertiary aliphatic amines, however, accelerate the polymerization rate, as do tertiary aromatic amines. Previous correlations of the ionization potentials (IP) of quenching agents and the rate of quenching of the ketone triplet state, [6,7] suggested that the reaction of an amine with an excited ketone involves electron transfer followed by proton transfer. Cook, observing a lack of this type of correlation for the CQ-amine systems, suggested that the conversion of the exciplex obtained after electron transfer into free radicals depends on the amine structure.…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary aliphatic amines, however, accelerate the polymerization rate, as do tertiary aromatic amines. Previous correlations of the ionization potentials (IP) of quenching agents and the rate of quenching of the ketone triplet state, [6,7] suggested that the reaction of an amine with an excited ketone involves electron transfer followed by proton transfer. Cook, observing a lack of this type of correlation for the CQ-amine systems, suggested that the conversion of the exciplex obtained after electron transfer into free radicals depends on the amine structure.…”
Section: Introductionmentioning
confidence: 99%
“…We were also unable to detect T 1 -T n absorption at 520 nm, where the triplet is known to absorb, 23 and previously was detectable by Truscott and co-workers only in the presence of a triplet sensitizer probed after a few microseconds delay. 23 Addition of triethylamine (TEA), a triplet quencher, [24][25][26] in a large excess (150:1 mole ratio) showed no decrease in the mid-IR signal observed. These combined observations strongly suggests that the 1509 cm -1 band does not represent triplet formation.…”
Section: Resultsmentioning
confidence: 99%
“…4,19,[25][26][27][28][29][30][31][32][33] Previous investigations of DCM 19,23,34 considered the formation of a TICT state involving rotation about the C-N bond linking the dimethylamino group to the aromatic ring, or rotation of the dimethylaminobenzyl moiety, but these experiments lacked any direct probe of structural change. Another proposed state is one analogous to the P* state 26,30,35 of stilbenes in which the molecule adopts a perpendicular conformation about the central double bond as an intermediate between cis and trans configurations. Electronic structure calculations for DCM using CS INDO have been able to locate a singlet state with a dipole moment large enough match the experiment, and in this state DCM adopts a configuration in which the dimethylamino moiety is perpendicular to the aromatic ring.…”
Section: -16mentioning
confidence: 99%
“…This result is compatible with our hypothesis that EB reacts with 1 O 2 to form a dioxetane intermediate. Indeed, the decomposition of such an intermediate would be expected to yield excited state carbonyl moieties, predominantly in the triplet manifold (60), which are prone to electron transfer with primary amines, acting as electron donors (63). Therefore, different final photoproduct(s) for EB compared to PBS could be obtained in TBS.…”
Section: Photobleaching In Tris Saline Buffer (Tbs)mentioning
confidence: 99%